The Effect of Kaizen Culture On Empolyee Performance in The Service Department at PT Megatama Mandiri Bekasi - Sawqi Saad El Hasan; Usman HM; Nurul Iman Maulana (Sharia Business Management Department of STEBIS Bina Mandiri, 2022)
As one of the service companies needed a very strict operating procedure in order to always provide good service through results quality goods produced by PT Megatama Mandiri Bekasi. To achieve optimal work results, then high performance is needed and this is where organizational culture has a very important role important in influencing employee performance. The purpose of this research is to find out the Cultural Influence Kaizen on Employee Performance at PT Megatama Mandiri Bekasi”. Quantitative research methods use the analysis is descriptive, and analytic with validity, reliability, T, rank correlation, and determination with a sample of 30 employees of PT Megatama Mandiri Bekasi. The result of kaizen culture which consists of education and training effect on increasing employees to best effort with kaizen spirit.